All men become brothers – The use of kinship terms for non-related persons as a sign of respect or disrespect - Hentschel, Elke (Linguistik Online, 2012)
In many different languages, kinship terms can be used in order to address or refer to non-kin. These terms can be very polite, and in many languages this is the only meaning and function they have. However, in some languages terms with the same meaning can be very impolite. This article shows how these differences can be explained by the nature of the underlying cultural concepts. In addition, it explores the question why kinship terms are used at all, be it in a polite or impolite way, in order to talk to or about non-related people.